(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2026)
This article provides an in-depth analysis of the Presidential Decree of the Republic of Uzbekistan dated October 20, 2025, “On Additional Measures for the Further Development of the State Language.” The decree defines the social, pedagogical, scientific, and technological directions for the development of the state language and aims to ensure its effective use across all sectors. The article highlights priority areas such as improving the quality of teaching the Uzbek language within the education system, developing new curricula and resources for general and higher education institutions, preserving linguistic purity and expanding vocabulary, and digitizing the state language through the use of modern information technologies and artificial intelligence.